Naturmangfoldloven - vern av løse og "faste" kulturminner fra andre verdenskrig som del av særpreget og karakteren til landskapsvern-områder - Farstadvoll, Stein; Nilsen, Gørill (Primitive Tider, 2020)
One of the main purposes of The Act of 19 June 2009 No.100 Relating to the Management of Biological, Geological and Landscape Diversity is to protect landscape diversity. Consequently, protection of cultural heritage is also an integrated part of the management of Landscape Protection Areas. Via a case study of the Second World War Luftwaffe storage site at Gjøkåsen, which is part of Øvre Pasvik Landscape Protection Area in Sør-Varanger Municipality, Troms and Finnmark County, the article discusses the difference between sites and objects and how this distinction may influence how or if remains from the Second World War gain legal protection under The Nature Diversity Act. The article concludes that in the future a potentially "greener" management of cultural heritage in Norway must employ an environmental approach where nature and culture are interwoven and not antonymic concepts.